The Greek shamans, the Scythian Psychonauts and the Spirit of Eranos - Putnik Noel (Glasnik Etnografskog Instituta SANU)
The paper provides a critical review of the influential theory on shamanistic elements in the religion of the ancient Greeks of the archaic period. The theory was developed during the first half of the 20th century, mainly through the efforts of classical philologists Karl Meuli and E. R. Dodds, and is based on the thesis that, during the colonization of the Black Sea coast, the Greeks adopted from the Scythians a specific form of ecstatic religiosity that was previously unknown to them. Meuli and Dodds characterized this form of religiosity as shamanistic, recognizing its patterns in a wide range of Greek mythological and legendary figures and historical personalities. By analyzing the theoretical premises and methodological approaches of these scholars, as well as the scientific community’s feedback, I aim to contextualize the thesis of Greek shamanism more closely within the intellectual currents of the twentieth century and earlier periods. My conclusion is that this thesis must be viewed in the broader context of the desacralization of contemporary society, indicating a strong interweaving of personal, non-scientific, and religious beliefs with academic studies of religions.